The effectiveness of particle dampers under centrifugal loads - Els, Daniel Nicolaas Johannes (Stellenbosch : University of Stellenbosch, 2009)
Thesis (PhD (Mechanical and Mechatronic Engineering))--University of Stellenbosch, 2009.